Upper Gastrointestinal Endoscopic Findings of Patients Presnting with Dyspepsia in Diyala Province - Almissari, Ahmed M Athab (Diyala Journal of Medicine, 2019)
Introduction: Endoscopy of upper gastrointestinal tract is a safe and easily carried out procedure of high diagnostic value and also atheraputic value in some cases. Endoscopy is not costly and has aremarkable low incidence of morbidity, Dyspepsia is a non-specific group of symptoms related to the upper GI tract. It is the medical term for indigestion, a symptom that includes epigastric pain, heartburn, distension, nausea or 'an acid feeling' occurring after eating or drinking. The symptom is subjective and frequent. The most common causes of indigestion are gastroesophageal acid reflux and functional dyspepsia. Other cases are a consequence of a more serious organic illness [6]. Objective: To evaluate the common causes of dyspepsia by endoscopic examination. Material and methods: Atotal of (9785) endoscopic examination of upper GI tract were recorded and analyzed during the period between first of January 1998 to end of December 2009. Results: The endoscopic findings of (9785) patients with dyspepsia were studied. Out of 9785 patients, 5112 patients (52.24%) were males while 4673(47.76%) were females. The endoscopic findings were normal in (3219) patients (32.89%). The abnormal findings included duodenal lesion in 3793 patients(38.76%) ,gastric lesions in 1492 patients (15.24%) ,esophageal lesions in 1111 patients(11.35%) and others causes in 170 paients(1.73%). Conclusion: The upper gastrointestinal endoscopy has ahigh diagnostic values in the investigations of upper gastrointestinal symptoms